2022
DOI: 10.3390/children9111743
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Pediatric Primary Healthcare Visits in a University-Based Primary Healthcare Center in Saudi Arabia

Abstract: This study aimed to identify the characteristics of pediatric primary health care (PHC) visits and evaluate the outcomes of patients presenting with complaints along with their referral and consultation capabilities. This was a retrospective medical record-based study. The study population included any pediatric patient (≤14 years old), including females and males, Saudis, and non-Saudis. Research data were gathered for visits from 2016–2021. Sampling was performed using a stratified random sample based on age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The respondents’ mean age was 37.1 ± 13.9 years, ranging from 18 to over 45 years. This research included parents with children below the age of 12, in contrast to Yousef et al’s study in which the sample encompassed children aged 14 and above [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…The respondents’ mean age was 37.1 ± 13.9 years, ranging from 18 to over 45 years. This research included parents with children below the age of 12, in contrast to Yousef et al’s study in which the sample encompassed children aged 14 and above [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, "follow-up" was one of the top complaints in pediatric consults in a primary care facility in Iran, a low-to-middle income country (LMIC) like the Philippines. 19,22,23 This finding suggests that it is important to include "follow-up" as an outcome to be reported in future studies in order to determine the rate at which patients are reassessed after initial consult and intervention by a primary care provider. The study by Liberman et al showed a low follow-up rate of 23.6% within seven days in pediatric patients with respiratory symptoms seen in primary care facilities in Washington DC.…”
Section: Discussionmentioning
confidence: 99%
“…Fever is a cause of discomfort for children and also causes anxiety for the parents as it affects the budget of the Health system. 1,2 Every year about 70% of preschool children suffer from this issue which causes disturbance in their activities, hunger and sleep problems in the affected children. Respiratory tract infections are common in winter and are mostly associated with fever and self-limiting infection of the respiratory tract.…”
Section: Introductionmentioning
confidence: 99%